Ein Königreich für Kohle? - Inwertsetzungs- und Propertisierungsprozesse an der Weltkulturerbelandschaft Mapungubwe (Südafrika) - Bergs, Caren (Universitätsverlag Göttingen, 2017)
The South African UNESCO world heritage site of Mapungubwe Cultural Landscape became the site of a conflict in 2011, when a coal mine was built in close proximity. The area of tension evolved around matters of conservation of culture, socio-economic development, environmental and nature protection, as well as the generation of identity. Following the conflict and its actors, the author shows the valorisation/valuation of Mapungubwe's resources as well as processes of propertisation against the backdrop of the special obstacles after the end of apartheid. Utilising interdisciplinary research approaches and an understanding of resource as a relational assemblage, the author follows the shifting of discourses between conservation of culture and extraction of resources from the local to the international level. She shows that power of interpretation is bound to time, place and actors when it comes to constituting cultural property.